Development and performance analysis of a novel 4 axis MPAW-based WAAM system - Rosli, Nor Ana (2023)
Additive Manufacturing (AM) is a process that creates free-form structures by layering material. Wire Arc Additive Manufacturing (WAAM) is a promising technique for fabricating large-scale metal structures with high deposition rates among the several AM techniques. However, excessive heat input in conventional arc welding used for WAAM has drawbacks in deposition resolution and surface finish. The use of non-consumable tungsten electrodes requires an external wire feeding, and the need to supply from the same direction during deposition has led to complicated path planning. Most WAAM systems used industrial robots as the motion mechanism but it increases the cost required to fabricate the metallic structure. This study aims to develop a low-cost 4-axis micro plasma arc welding (MPAW) based WAAM system. The systems incorporate 4 axis 3D printer as a motion mechanism and MPAW as a heat source to address this issue. The study develops the 4-axis 3D printer which consists of three linear axes (X-axis, Y-axis, Z-axis) and one rotational axis (A-axis). The advantage of using MPAW is the current usage is less or equal to 20A current. Additionally, an external wire feeding system is integrated with 4 axis MPAW-based system to deliver wire material. The wire feeding angle from the preliminary finding was found of 60° to deliver constant metal bridging transfer mode. The optimising design of the experiment (DOE) for single bead deposition was performed using response surface methodology (RSM) to achieve the maximum bead height, H and bead width, W, and minimum bead roughness (Ra). The optimal input parameter was 36.63 mm/min of wire feed speed, 64.86 cm/min of welding speed, and 100% welding pulse with desirability of 0.537. Multilayer linear structure is successfully fabricated with the optimal parameters and its morphology, microstructure, and mechanical properties were investigated. The result indicated the morphology feature is free from cracks and apparent defects or pores. The microstructure of multilayer linear structure exhibits a non-uniform microstructure and mainly consists of the cellular dendrite, columnar dendrite, and equiaxed dendrite. The transformation occurs due to the multiple thermal cycle and reduction of the temperature gradient. The average microhardness value is highest at the bottom at 209.152 HV and gradually decreases at the middle and increases towards the top. Moreover, the ultimate tensile strength is also highest at the bottom with an average of 670.082 MPa. The result of the fractured image through SEM revealed a fine dimple structure formed at the bottom and large dimple structure at the top region. Compared with other WAAM processes, the 4-axis MPAW-based WAAM system tensile strength is the highest. Lastly, the 4-axis MPAW based WAAM system was validatd by low dimension difference percentage errors between CAD model and fabricated structures (rectangular, cylinder, curve, and vase). Thus, the study successfully develop the new low-cost 4-axis MPAW-based WAAM system. A better understanding of single-layer deposition, multilayer deposition, and the effect on structure fabrication is supported.